White-rot fungi capable of decolourising textile dyes under alkaline conditions - Ottoni, C. A. (2013)
Twelve white-rot fungal strains belonging to seven different species were screened on plates under alkaline condition to study the decolourisation of the textile dyes Reactive Black 5 and Poly R-478. Three strains of Trametes versicolor (Micoteca da Universidade do Minho (MUM) 94.04, 04.100 and 04.101) and one strain of Phanerochaete chrysosporium (MUM 94.15) showed better decolourisation results. These four strains were used for decolourisation studies in liquid culture medium. All four selected strains presented more efficient decolourisation rates on Reactive Black 5 than on Poly R-478. For both dyes on solid and liquid culture media, the decolourisation capability exhibited by these strains depended on dye concentration and pH values of the media. Finally, the decolourisation of Reactive Black 5 by T. versicolor strains MUM 94.04 and 04.100 reached 100 %. In addition, the highest white-rot fungi ligninolytic enzyme activities were found for these two strains.